Early Work: Path Selection in a Path-aware Network Architecture - Krüger, Thorben; Hausheer, David (Electronic Communications of the EASST, 2021)
Modern path-aware networking (PAN) architectures based on packet-carried forwarding state (PCFS) promise to support practical multipath communication with increased availability and redundancy, even for single-homed hosts. How exactly hosts can chose paths in a meaningful way while maintaining good network utilization as well as user satisfaction is the subject of this research. We demonstrate how overall network utilization is affected by the introduction of multipath communication and propose the term “Cost of Multipath” to reason about this observation. We also identify a collection of concrete practical techniques from networking research and engineering that can be adapted to allow hosts to make more informed path decisions. These tie into the practical implementation of an experimental path-selection engine with a high-level API that we aim to utilize to quantitatively investigate host-based approaches for traffic optimization in the existing path-aware SCION network architecture